Enterprise Performance Management (EPM) and the Digital Revolution. Issue 4 (April 2017) - Cokins, Gary
Abstract : Digital transformation is threatening the viability of organizations. There is increasing volatility and uncertainty from globalization. Enterprise and corporate performance and management (EPM/CPM) methods are now viewed as the seamless integration of managerial systems. Each method should be embedded with business analytics of all flavors, such as correlation, segmentation, regression and clustering analysis, and especially predictive analytics as a bridge to prescriptive analytics to yield the best (ideally optimal) decisions.